Membangun Daya Saing Institusi Pendidikan Berbasis Kompetensi Dasar Organisasi - Edy Suandi Hamid (Universitas Islam Indonesia, 2008)
This article is intended to discuss some experiences of the Islamic University of Indonesia (Universitas Islam Indonesia, here in after UII) in developing its core competences as the main source of competitiveness to face higher education changes and challenges. This article reveals that the UII has developed its core competences mainly in the arts of management and governance of the university. The UII has introduced a more simple but flexible structure of management in all units, in order to reduce cost and to fasten decision making process. Using such a management and governance, the UII has developed its main activities based on its mission to promote Islamic values, as blessing for all creatures. This article suggests that universities, especially those of Islamic ones, develop their core competences based on management and govemance issues, such as the real world challenges, commitments, and Islamic values.